PENGARUH MUTU PELAYANAN TERHADAP MINAT KUNJUNGAN ULANG PASIEN RAWAT INAP DI RUMAH SAKIT SURYA INSANI PASIR PENGARAIAN RIAU TAHUN 2019 - Rahma Dona; Arifah Devi Fitriani; Nur Aini (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2019)
THE EFFECT OF SERVICE QUALITY ON INTEREST REVIEW OF PATIENTS IN SURYA INSANI HOSPITAL PASIR PENGARAIAN RIAU 2019 RAHMA DONA NIM : 1602011060 Hospital services as one of the fields of service that plays an important role. The main indicator to determine hospital standards is patient satisfaction with hospital services. Based on the results of interviews of 20 patients at the Surya Insani Pasir Pengaraian Hospital in Riau showed that all patients were still not satisfied with the services provided by the hospital so they were not interested in making a repeat visit. The purpose of this study was to determine the effect of service quality on the interest of inpatient visits at Surya Insani Pasir Pengaraian Hospital in Riau. The research design used in this study is Cross Sectional. The population in this study were 320 patients and samples taken by accidental sampling were 178 people. Data collection methods are primary data and secondary data. Analysis of the data used is binary logistic regression test. The results showed that professionalism has a sig-p value of .003 < .05, efficiency has a sig-p value of .000 < .05, security has a sig-p value of .003 < .05 and satisfaction has a sig-p value of .000 < .05, which means it has an influence on the interest of inpatient visits. For the facility variable has a sig-p value of .108 > .05, which means that the facility has no influence on the interest of inpatient visits. The conclusion in this study there is the influence of professionalism, efficiency, safety and satisfaction with the interest of visiting inpatients, while the facility has no influence on the interest of visiting inpatients. Suggestions for hospitals are expected to be a reference in order to better understand the importance of quality services in accordance with the regulations of the ministry of health in order to optimally improve the health services provided to patients, through increasing the professionalism of health workers, efficiency, safety, satisfaction and facilities at the hospital. Keywords : Service Quality, Revisiting Interests, Inpatients Bibliography : 28 Books + 35 Journals (1988-2019)